Histamine H3 receptor antagonists/inverse agonists on cognitive and motor processes: relevance to Alzheimer's disease, ADHD, schizophrenia, and drug abuse - Vohora, Divya; Bhowmik, Malay (Frontiers in Systems Neuroscience, 2012)
Histamine H3 receptor antagonists/ inverse agonists possess potential to treat diverse disease states of the central nervous system (CNS). Cognitive dysfunction and motor impairments are the hallmark of multifarious neurodegenerative and/or psychiatric disorders. This review presents the various neurobiological/ neurochemical evidences available so far following H3 receptor inverse agonists/ antagonists in the pathophysiology of Alzheimer’s disease (AD), attention-deficit hyperactivity disorder (ADHD), schizophrenia and drug abuse each of which is accompanied by deficits of some aspects of cognitive and/or motor functions. Whether the H3 receptor inverse agonism modulates the neurochemical basis underlying the disease condition or affects only the cognitive/motor component of the disease process is discussed with the aim to provide a rationale for their use in diverse disease states that are interlinked and are accompanied by some common motor, cognitive and attentional deficits.